Princess Academy - Hale, Shannon (New York : Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2007)
While attending a strict academy for potential princesses with the other girls from her mountain village, fourteen- year-old Miri discovers unexpected talents and connections to her homeland.
"First published by Bloomsbury U.S.A. Children's Books in 2005" --Verso.
Includes author interview and reading group guide.
890
Accelerated Reader AR
Keywords: Princesses -- Juvenile fiction; Self-confidence -- Juvenile fiction; Telepathy -- Juvenile fiction; Mountains -- Juvenile fiction; Schools -- Juvenile fiction; Princesses -- Fiction; Self-confidence -- Fiction; Telepathy -- Fiction; Mountains -- Fiction; Schools -- Fiction